Comparative Analysis of Basic Anti-Asthmatic Therapy in High-Altitude Conditions in Children Suffering from Bronchial Asthma - L. A. Temmoeva; Z. A. Kambachokova; M. Z. Tlupova; N. M. Temmoev; M. I. Almatova; D. Kh. Abdulvakhidova; M. S.-E. Akhmadova; M. A. Atueva; Kh. A. Akhmatkhanova; K. M. Dakhova; A. A. Poroshina; L. M. Murzakanova; et al. (Антибиотики и Химиотерапия)
The article presents the features of the psychoemotional status, vegetative regulation, as well as correction methods for adolescents with bronchial asthma. For an objective assessment of the psycho-emotional state of children, the course of the disease was studied during the basic anti-asthmatic therapy and in combination with altitude climate therapy. Corrective work was carried out using various psychological techniques. Prognostically significant factors in the course of bronchial asthma were objectified using comparative pathopsychological and mathematical analysis.